Pengaruh POC Kotoran Tenebrio molitor dan AB Mix terhadap Selada (Lactuca sativa L.) dalam Hidroponik Wick: - - Afidatul Mufarihah Khotijah; Eko Budi Minarno; Muhammad Asmuni Hasyim (Universitas Muhammadiyah Kotabumi, 2026)
Lettuce (Lactuca sativa L.) is a highly nutritious vegetable with increasing consumption due to population growth and rising awareness of healthy diets. However, its production is constrained by limited agricultural land, prompting the need for alternative cultivation methods such as hydroponics. The wick hydroponic system is a simple, low-cost method suitable for small-scale or household farming. This study aimed to examine the effect of combining liquid organic fertilizer (POC) from frass mealworm (Tenebrio molitor) with AB Mix on the growth and yield of lettuce in a wick hydroponic system. The POC used in this research contained total nitrogen (N) of 2.7%–7.8%, phosphorus (P) of 1.0%–1.5%, and potassium (K) of 1.2%–2.0%. A completely randomized design was used with five treatments: P0= 100% AB Mix, P1= 25% POC + 75% AB Mix, P2= 50% POC + 50% AB Mix, P3= 75% POC + 25% AB Mix, and P4= 100% POC, each repeated four times. Parameters observation included number of leaves, total chlorophyll content, photosynthesis rate, and plant fresh weight. Data were analyzed using SPSS version 22. Outcomes revealed that the combination of POC and AB Mix significantly affected several growth parameters. The evidence obtained from the study suggests that the combination of POC and AB Mix affected group treatment. The best concentration is the combination of 25% POC and 75% AB Mix for the parameters of the number of leaves and total chlorophyll content.